ANALYTICAL METHOD DEVELOPMENT FOR SIMULTANEOUS DETERMINATION OF UBIDECARENONE AND VITAMIN E ACETATE IN CAPSULE DOSAGE FORM BY HPLC - Grace, A. Caroline; Prabha, T.; Jagadeeswaran, M.; Srinivasan, K.; Sivakumar, T. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: To develop and validate a new simple, accurate, precise and sensitive high performance liquid chromatographic method (HPLC) method for simultaneous estimation of ubidecarenone and vitamin E acetate in capsule dosage form as per international conference on harmonization (ICH) guidelines. Methods: The chromatographic separation of drugs were achieved using hypersil C8 column (250 mm x 4.6 mm, 5µ) in isocratic elution mode with a mobile phase of methanol: ethanol: n-hexane (80:10:10 v/v/v) at a flow rate of 1 ml/min with ultra-violet (UV) detection at 210 nm. Results: The optimized method produced sharp peaks with good resolution, minimum tailing factor and satisfactory retention time were found to be 5.745 min and 12.565 min for vitamin E acetate and ubidecarenone respectively. The method was linear in the range of 60-180 µg/ml for ubidecarenone and 20-60 µg/ml for vitamin E acetate with a correlation coefficient of 0.999 and 0.9993 respectively. Mean recoveries observed for ubidecarenone and vitamin E acetate were 99.85% and 99.73% respectively. The percentage relative standard deviation (% RSD) of peak area for system precision, method precision, and intermediate precision were found to be less than 0.37%. The lower degree of % RSD obtained has proved that the method was precise and robust. Conclusion: A new simple HPLC method was developed and validated as per ICH guidelines for the simultaneous estimation of ubidecarenone and vitamin E acetate and the method can be effectively applied for the routine analysis of active pharmaceutical ingredient (API) and formulations.